Studies of biodiesel production using various blends of waste palm cooking oil and castor oil - Rao Geevitha Anantha; Krishnan Soundarajan (E3S Web of Conferences)
This study has been conducted using blends of castor oil (CO) and waste palm cooking oil (WPCO) in different proportions to enhance % yield of biodiesel via transesterification. The effects of various blending ratios of WPCO: CO (wt.%), molar ratios of methanol: oil, catalyst concentrations (wt.%), reaction time, reaction temperature and various co-solvents have been investigated to determine the optimal conditions for transesterification reaction. Maximum % yield of biodiesel is obtained at 75:25 (wt.%) of WPCO:CO blend, 9:1 methanol to oil ratio, 1 wt.% KOH catalyst, reaction temperature of 32°C, reaction time of 30 min, using n-hexane as co-solvent. The highest obtained biodiesel yield is 96%. Analysis confirmed 25 FAME components, and the fuel met ASTM standards. Blending non-edible feedstocks for biodiesel production is a sustainable approach to reduce costs and environmental impact.